USING COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH THROUGH SMALL GROUP DISCUSSION AS A DEVICE TO STIMULATE THE STUDENTS TO SPEAK IN ENGLISH - Setiadi, Muhammad Astrianto (EXPOSURE JOURNAL, 2012)
This study was conducted to find out whether or not the using of Communicative Language Teaching (CLT) Approach through Small Group Discussion effective to stimulate the students to speak in English than the conventional way, and also to improve the teacher awareness to use an effective approach in teaching English especially in teaching speaking skill. This study employed a Pre-Experimental research method with One Group Pre-test and Post-test Design. The data obtained from the test was analyzed quantitatively and then itâs result was compared with questionnaire to know whether the students interested in learning speaking by using Communicative Language Teaching (CLT) Approach or not. The mean score obtained from Pre-test was 2, 84 and post-test was 6, 01. The data showed that the studentâs speaking skills in post-test was higher than the pre-test. The data obtained from questionnaire showed the mean score 78, 67. It means that the students were highly interested to the application of speaking materials through Communicative Language Teaching Approach through small group discussion.Keyword: Communicative Language Teaching Approach, Small Group discussion, speaking.Penelitian ini dilakukan untuk mengetahui penggunaan dari Pengajaran Pendekatan Bahasa Komunikatif (CLT) melalui Diskusi Kelompok Kecil efektif untuk merangsang siswa untuk berbicara dalam bahasa Inggris dari pada cara konvensional, dan juga untuk meningkatkan kesadaran guru untuk menggunakan pendekatan yang efektif dalam mengajar bahasa Inggris terutama dalam mengajar keterampilan berbicara. Penelitian ini menggunakan metode penelitian Pre-Eksperimental dengan Satu Group Pre-test dan Post-test Design. Data yang diperoleh dari tes dianalisis secara kuantitatif dan kemudian itu hasil itu dibandingkan dengan kuesioner untuk mengetahui apakah siswa tertarik untuk belajar berbicara dengan menggunakan Pendekatan Pengajaran Bahasa Komunikatif (CLT) atau tidak. Skor rata-rata yang diperoleh dari Pre-test adalah 2, 84 dan post-test adalah 6, 01. Data menunjukkan bahwa keterampilan berbicara siswa dalam post-test lebih tinggi dari pre-test. Data yang diperoleh dari kuesioner menunjukkan mean skor 78, 67. Ini berarti bahwa siswa yang sangat tertarik untuk penerapan bahan berbicara melalui Pengajaran Bahasa Komunikatif Pendekatan melalui diskusi kelompok kecil.Kata Kunci: Komunikatif Pengajaran Bahasa Pendekatan, diskusi kelompok kecil, berbicara.